2011
DOI: 10.1007/s00702-011-0609-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare brain biopsy findings in a first ADEM-like event of pediatric MS: histopathologic, neuroradiologic and clinical features

Abstract: Pediatric MS tends to present more often with an acute onset and a polysymptomatic form of the disease, possibly with encephalopathy and large tumefactive lesions similar to those observed in some cases of acute disseminated encephalomyelitis (ADEM), which makes it more difficult to differentiate between an explosive and severe onset of MS vs. ADEM. An ADEM-like first demyelinating event can be the first attack of pediatric MS, but international consensus definitions require two or more non-ADEM demyelinating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[ 18 ] Adolescent ADEM may have comorbid TDLs. [ 19 ] Poser and Brinar believed that TDL is a phenotypic variant of classic MS and so did Lolekha and Kulkantrakorn. [ 20 ] Recently, studies in China and other countries showed that most of the TDLs were monophasic, and some cases of TDLs may transform to relapsing-remitting MS (RRMS)[ 2 17 ] or take the form of recurrent TDLs.…”
Section: Linical C Haracteristicsmentioning
confidence: 99%
“…[ 18 ] Adolescent ADEM may have comorbid TDLs. [ 19 ] Poser and Brinar believed that TDL is a phenotypic variant of classic MS and so did Lolekha and Kulkantrakorn. [ 20 ] Recently, studies in China and other countries showed that most of the TDLs were monophasic, and some cases of TDLs may transform to relapsing-remitting MS (RRMS)[ 2 17 ] or take the form of recurrent TDLs.…”
Section: Linical C Haracteristicsmentioning
confidence: 99%
“…The pathophysiology is still unclear and probably involves a transient autoimmune response directed at myelin or other self-antigens, possibly by molecular mimicry or by nonspecific activation of autoreactive T cell clones [2,10]. Brain biopsies are performed in difficult cases [7,8]. Histologically, ADEM is characterized by perivenous demyelination and infiltration of the vessel wall and perivascular spaces by lymphocytes, plasma cells, and monocytes [4].…”
Section: Discussionmentioning
confidence: 99%
“…The injury to the CNS may be mediated by the cytotoxic CD8+ T cells that remain unregulated. The injury may result in large tumefactive lesions in the brain, quite similar to the large lesions of acute disseminated encephalomyelitis (ADEM)-like event described in pediatric MS reported to be mediated by cytotoxic CD8+ T cells [ 19 ]. If the mechanism of CNS injury with the characteristic tumefactive lesions is primarily mediated by CD8+ T cells, DMF which is known to preferentially deplete the CD8+ T cell population [ 20 ] could be helpful in mitigating the fingolimod rebound phenomenon.…”
Section: Discussionmentioning
confidence: 99%